Upaya Guru Bahasa Jawa dalam Menerapkan Unggah-Ungguh Basa pada Mata Pelajaran Bahasa Jawa Kelas X Semester Gasal di SMA Negeri 3 Brebes - Ambarwati, Ambarwati -; Alfiah, Alfiah -; Zaidah, Nuning (JISABDA: Jurnal Ilmiah Sastra dan Bahasa Daerah, Serta Pengajarannya, 2022)
The background of this research is that there are still many teachers who have not used good efforts or methods in applying upload-ungguh basa to students. The formulation of the problem that can be taken is how the Javanese language teacher's efforts in implementing upload-ungguh basa in class X odd semester Javanese language subjects at SMA Negeri 3 Brebes and the obstacles encountered by the Javanese language teacher in applying upload-ungguh basa to students. The purpose of this study is to describe the form of the Javanese language teacher's efforts in applying upload-ungguh basa in class X odd semester Javanese language subjects at SMA Negeri 3 Brebes and to describe the obstacles encountered by the Javanese language teacher in applying upload-ungguh basa to students. This research is a descriptive type of research, with a qualitative approach. Sources of research data are Javanese language teachers and odd semester X grade students of SMA Negeri 3 Brebes with research data in the form of descriptions of observations, interviews and documentation conducted with Javanese language teachers and odd semester X grade students of SMA Negeri 3 Brebes. The data analysis technique uses data reduction, data presentation and conclusions. After analyzing the data, several research results were found as follows: the efforts made by Javanese language teachers in applying upload-ungguh basa to students include, 1) providing and conveying knowledge about upload-ungguh basa; 2) familiarize students with using the appropriate Javanese language when communicating; 3) conduct questions and answers to students using upload-ungguh base; 4) provide examples to students on how to behave well; 5) explain the learning material using the Javanese language. The obstacles encountered by the teacher when implementing the upload-ungguh base of students include: 1) the low awareness of students about the importance of learning the Javanese language; 2) many young people consider Javanese to be an ancient language; 3) students use Indonesian in everyday.